Perception of History Teachers of Independent Learning Curriculum at Man 2 Pekanbaru - Berliana Sari, Bunga (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The purpose of this research is to find out the perception of History teachers towards the independent learning curriculum at MAN 2 Pekanbaru, to find out what obstacles history teachers face in implementing the independent learning curriculum at MAN 2 Pekanbaru, and to find out what efforts are made by history teachers against obstacles that occur in implementing the independent learning curriculum at MAN 2 Pekanbaru. This research uses qualitative research methods, with data collection techniques in the form of observation, interviews, and documentation. The subjects in this study were 3 history teachers. The results in this study indicate that History teachers at MAN 2 Pekanbaru have a fairly good perception of the independent learning curriculum. The obstacles faced by History teachers are the lack of government socialization before the implementation of the independent learning curriculum and the lack of preparation from teachers. The efforts made by History teachers to overcome the obstacles that occur are by attending training held by madrasah and by studying the independent learning curriculum on the internet.